2021
DOI: 10.3390/antiox11010003
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins and Sepsis: Cross Talk between Redox and Epigenetic Pathways

Abstract: Sepsis and septic shock are the leading causes of death among hospitalized patients in the US. The immune response in sepsis transitions from a pro-inflammatory and pro-oxidant hyper-inflammation to an anti-inflammatory and cytoprotective hypo-inflammatory phase. While 1/3rd sepsis-related deaths occur during hyper-, a vast majority of sepsis-mortality occurs during the hypo-inflammation. Hyper-inflammation is cytotoxic for the immune cells and cannot be sustained. As a compensatory mechanism, the immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 204 publications
(262 reference statements)
0
4
0
1
Order By: Relevance
“…PKM2-dependent aerobic glycolysis promoted macrophages stimulated by lipopolysaccharide to release HMGB1 and IL-1β ( Xie et al., 2016 ). Numerous studies have indicated that immunosuppression was a factor for increased susceptibility to mortality and secondary infection in sepsis, and most sepsis-mortality occurred in hypo-inflammation ( Gandhirajan et al., 2021 ; Torres et al., 2022 ). Severe depletion of dendritic cells might be used to predict sepsis outcome in the early stage ( Weber et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…PKM2-dependent aerobic glycolysis promoted macrophages stimulated by lipopolysaccharide to release HMGB1 and IL-1β ( Xie et al., 2016 ). Numerous studies have indicated that immunosuppression was a factor for increased susceptibility to mortality and secondary infection in sepsis, and most sepsis-mortality occurred in hypo-inflammation ( Gandhirajan et al., 2021 ; Torres et al., 2022 ). Severe depletion of dendritic cells might be used to predict sepsis outcome in the early stage ( Weber et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is capable of histone deacetylation to regulate chromatin function and promote alterations in histone and DNA methylation, leading to transcriptional repression through its anti-inflammatory and antioxidant properties and regulation of the sepsis-induced immune response. 97 Further, metabolic shifts are controlled by AMPK disruption of mTOR-dependent protein synthesis and combined sirtuin 1, 3, and 6 reactions that support catabolic energizers. 98 SIRT1 promotes heterochromatin formation and NF-κB inactivation of key inflammatory genes such as TNF and IL-1β.…”
Section: Immunosuppression Of Sepsismentioning
confidence: 99%
“…Emerging evidence supports the role of sirtuins (SIRT1-7) in the progression and prognosis of sepsis acting on epigenetic profile [ 39 42 ], even if the involvement of SIRT4 in endothelial septic disorder is widely debated. Of note, SIRT4 emerges as a physiological player leading to hypo-inflammation and promoting sepsis recovery [ 43 ].…”
Section: Introductionmentioning
confidence: 99%